Climatic and psychosocial risks of heat illness incidents on construction site - Jia, Andrea; Rowlinson, S.; Ciccarelli, M. (Elsevier, 2016)
The Ergonomics Society. The study presented in this paper aims to identify prominent risks leading to heat illness in summer among construction workers that can be prioritised for developing effective interventions. Samples are 216 construction workers' cases at the individual level and 26 construction projects cases at the organisation level. A grounded theory is generated to define the climatic heat and psychosocial risks and the relationships between risks, timing and effectiveness of interventions. The theoretical framework is then used to guide content analysis of 36 individual onsite heat illness cases to identify prominent risks. The results suggest that heat stress risks on construction site are socially constructed and can be effectively managed through elimination at supply chain level, effective engineering control, proactive control of the risks through individual interventions and reactive control through mindful recognition and response to early symptoms. The role of management infrastructure as a base for effective interventions is discussed.